Symbol-error performance and bit-error performance of QAM signalling - Mohamad Humairan Mohamed Gazali (Nanyang Technological University, 2022)
While the overall situation has improved over time, the ongoing global pandemic continues to affect our lives especially in terms of how society interacts with one another. Thanks to advancements in communications technology, modern society (especially during the pandemic) has become reliant on digital communication systems in our everyday life by enabling us to be both locally and globally connected through devices such as our smartphones and laptops. Thus, it is important to ensure the information transmitted and received through these digital communication systems and devices are as error-free as possible. This report explores how different transmission techniques known as modulation schemes perform when subjected to transmission channel conditions involving additive white Gaussian noise (AWGN) and Rayleigh fading. In particular, the report will cover M-ary phase-shift keying (M-PSK), M-ary amplitude and phase-shift keying (M-APSK) and M-ary quadrature amplitude modulation (M-QAM) modulation schemes. Using MATLAB simulation, this project will evaluate the performance of the various modulation schemes under the channel conditions mentioned above by comparing the bit error rates (BER) and symbol error rates (SER) results obtained through the simulation.